Efektivitas Model Pembelajaran Blended learning terhadap Motivasi dan Tingkat Kompetensi Mahasiswa Mata Kuliah Meteorologi Klimatologi - Annisa Salsabilla; Dian Utami; Listumbinang Halengkara (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2020)
This study aims to see at student motivation arising from the application of the blended learning model, student competencies formed due to the application of the blended learning model, the effectiveness of the application of the blended learning model in increasing student motivation and competence in the meteorology climatology course, also providing references for the use of the model blended learning to other courses so that lectures can run effectively and efficiently. The method is a quasi-experiment method. The sample was student on their first semester in 2019 of the Geography Education Study Program in the Class of Meteorology Climatology. The results of the study are as follows: 1) The application of the blended learning model in the Climatology Meteorology Course in Geography Education Study Program students influences student motivation in learning. 2) The application of the blended learning model in the Climatology Meteorology Course for Geography Education Study Program students increases the level of student competency. 3) The blended learning model is one of the effective learning models for increasing student motivation and competence. This can be seen from the formed student motivation and increased student competence. 4) The use of the blended learning model can be applied to other subjects as an alternative so that lectures can run effectively and efficiently